Discrete Element Analysis Methods of Generic Differential Quadratures - Chen, Chang-New.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg, 2006)
This book presents numerical differential quadrature (DQ) - based methods recently developed by the author. Their ability for solving generic scientific and engineering problems is demonstrated. These methods are the generic differential quadrature, the extended differential quadrature and the related discrete element analysis methods. These novel numerical techniques are both efficient and reliable. They are suitable for developing solution algorithms for various computational mechanics problems with arbitrarily complex geometry. This is shown for several comprehensive examples such as bars and beams, trusses, frames, general field problems, elasticity problems or bending of plates.
Generalization of DQ $1 (BExtended Differential Quadrature -- DQEM Analysis of One-Dimensional Elasticity Problems -- DQEM Analysis of Euler-Bernoulli Beam Structures -- DQEM Analysis of Static Deflection of Three-Dimensional Trusses -- DQEM Analysis of Static Deflection of Three-Dimensional Frames -- DQEM Analysis of Vibration of Frames Considering Warping Torsion -- DQEM Analysis of Timoshenko Beam Structures -- DQEM Analysis of Curved Beam Structures -- Development of DQEM Irregular Elements -- DQEM Analysis of Two-Dimensional Steady-State Field Problems -- DQEM Analysis of Two-Dimensional Elasticity Problems -- DQEM Analysis of Kirchhoff-Love Plate Problems -- DQFDM Analysis -- Generalized Coordinate Differential Quadrature Element Method -- EDQ Based Direct Time Integration Methods.s
Keywords: Mathematics; Mathematical analysis; Analysis (Mathematics).; Physics; Computational intelligence; Mechanics; Mechanics, Applied; Mathematics; Analysis; Theoretical and Applied Mechanics; Computational Intelligence; Theoretical, Mathematical and Computational Physics; Mathematical Methods in Physics; Numerical and Computational Physics; Electronic books